Seleksi Tomatillo (Physalis ixocarpa Brot. ex Hornem) untuk Hibridisasi Berdasarkan Karakter Morfologi - Widyaelina, Ermila; Waluyo, Budi (Sekolah Tinggi Pertanian Kutai Timur, 2019)
ABSTRACT Tomatillo (Physalis ixocarpa Brot ex. Hornem) is a species of the Solanaceae family that was recently introduced in Indonesia. Tomatillo is consumed in a various preparation and has a high content of flavonoids, alkaloids, terpenes, vitamins A and C. Developed of tomatillo’s superior varieties from Indonesia has not been done. Tomatillo breeding needs to be done for the development of potential genotypes as the basis for the formation of new superior varieties. The purpose of this research was to determine the variability and grouping of tomatillo genotypes based on morphological characters. This research used 20 potential genotypes. Research was arranged based on augmented design, and observations were made on each plant. Genotype character variability was analyzed by Principal Component Analysis (PCA) using Pearson correlation coefficient approach, and grouping analysis was analyzed using Pearson correlation based on the similarity coefficient and the Unweighted Pair Group Average (UPGMA) agglomeration method. The results showed that there was a variability between characters of 90.62% obtained from 10 main components with 27 contributing morphological characters consisting of qualitative and quantitative characters. The 20 potential genotypes had similarity between genotypes at 89.4% and were divided into 3 groups at 96.4% similarity values. The genetic distance between the first and second groups was 0.026, between the second and third groups was 0.032, and between the first and third groups was 0.081. The genotypes that have the highest similarity are Pixo [P14] and Pixo [P22] and Pixo [G35] and Pixo [GY21]. Both pairs of genotypes have 99.5% similarity coefficient or genetic distance of 0.005. Genotypes that have the highest variability are Pixo [P35] and Pixo [GY11] with a similarity coefficient of 81.8% or have a genetic distance of 0.182. Keywords: Diversity, genetic distance, Tomatillo.